1998
DOI: 10.1074/jbc.273.44.29218
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Rap1 GTPase by the B Cell Antigen Receptor

Abstract: The B cell antigen receptor (BCR) activates Ras, a GTPase that promotes cell proliferation by activating the Raf-1/MEK/ERK signaling module and other signaling enzymes. In its active GTP-bound form, the Rap1 GTPase may act as a negative regulator of Ras-mediated signaling by sequestering Ras effectors (e.g., Raf-1) and preventing their activation. In this report, we show that BCR engagement activates Rap1 and that this is depend-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 35 publications
3
68
1
Order By: Relevance
“…Next, we wished to identify the signaling pathway that couples the SDF-1 receptor, CXCR4, to the activation of Rap1 and Rap2. We had previously shown that the B cell Ag receptor activates Rap1 via PLC-␥2-dependent production of DAG (32). Because chemokine receptor signaling leads to the PLC-␤-dependent production of DAG, we hypothesized that SDF-1 would activate Rap1 and Rap2 via this pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we wished to identify the signaling pathway that couples the SDF-1 receptor, CXCR4, to the activation of Rap1 and Rap2. We had previously shown that the B cell Ag receptor activates Rap1 via PLC-␥2-dependent production of DAG (32). Because chemokine receptor signaling leads to the PLC-␤-dependent production of DAG, we hypothesized that SDF-1 would activate Rap1 and Rap2 via this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Where indicated, the cells were pretreated with the PLC inhibitor U73122 or its inactive structural analog U73343 (BioMol, Plymouth Meeting, PA). The cells were solubilized and assayed for Rap activation as described previously (32). Briefly, a GST-RalGDS fusion protein was used to selectively precipitate the activated GTP-bound forms of Rap1 and Rap2, which were then detected by immunoblotting with anti-Rap1 (Santa Cruz Biotechnology, Santa Cruz, CA) or anti-Rap2 Abs (BD Transduction Laboratories, Lexington, KY).…”
Section: Rap1 Rap2 and Rac1 Activation Assaysmentioning
confidence: 99%
“…Engagement of the Fc⑀R leads to activation of the PLC␥ pathway, which, in turn, can promote and/or enhance activation of all three types of MAPKs, including ERKs, JNKs, and p38 MAPKs (29,30,35,44,45). Therefore, we evaluated the extent of ERK, JNK, and p38 MAPK activation in PLC␥2-deficient, relative to wild-type, mast cells in response to Fc⑀R cross-linking.…”
Section: Plc␥2-deficient Mast Cells Have Impaired Fc⑀r-induced Ca 2ϩ mentioning
confidence: 99%
“…It is not known how the TCR and Rap1 might connect to adhesionand degranulation-promoting adaptor protein signaling, but it is likely to involve Fyn and SLP-76 (54, 55) activating Rap1 via PLC , which contains a Ras-Rap-binding domain and can act as a guanine nucleotide exchange factor for Rap1 (57,58). Consistent with this, there is evidence that Rap1 activation after Ag-specific triggering of lymphocytes requires PLC activation and consequent calcium mobilization and 1,2-diacylglycerol generation (52,59,60).…”
Section: Discussionmentioning
confidence: 91%